Physiological and Proteomic Responses of the Tetraploid Robinia pseudoacacia L. to High CO2 Levels - Li, Jianxin; Zhang, Subin; Lei, Pei; Guo, Liyong; Zhao, Xiyang; Meng, Fanjuan (International journal of molecular sciences, 2024)
The increase in atmospheric CO2 concentration is a significant factor in triggering global warming. CO2 is essential for plant photosynthesis, but excessive CO2 can negatively impact photosynthesis and its associated physiological and biochemical processes. The tetraploid Robinia pseudoacacia L., a superior and improved variety, exhibits high tolerance to abiotic stress. In this study, we investigated the physiological and proteomic response mechanisms of the tetraploid R. pseudoacacia under high CO2 treatment. The results of our physiological and biochemical analyses revealed that a 5% high concentration of CO2 hindered the growth and development of the tetraploid R. pseudoacacia and caused severe damage to the leaves. Additionally, it significantly reduced photosynthetic parameters such as Pn, Gs, Tr, and Ci, as well as respiration. The levels of chlorophyll (Chl a and b) and the fluorescent parameters of chlorophyll (Fm, Fv/Fm, qP, and ETR) also significantly decreased. Conversely, the levels of ROS (H2O2 and O2·−) were significantly increased, while the activities of antioxidant enzymes (SOD, CAT, GR, and APX) were significantly decreased. Furthermore, high CO2 induced stomatal closure by promoting the accumulation of ROS and NO in guard cells. Through a proteomic analysis, we identified a total of 1652 DAPs after high CO2 treatment. GO functional annotation revealed that these DAPs were mainly associated with redox activity, catalytic activity, and ion binding. KEGG analysis showed an enrichment of DAPs in metabolic pathways, secondary metabolite biosynthesis, amino acid biosynthesis, and photosynthetic pathways. Overall, our study provides valuable insights into the adaptation mechanisms of the tetraploid R. pseudoacacia to high CO2.